Development of novel synthetic muscle tissues for sports impact surrogates. (January 2015) - Payne, Thomas; Mitchell, Séan; Bibb, Richard; Waters, Mark
Abstract: Impact injuries are commonplace in sport and often lead to performance detriment and debilitation. Personal Protective Equipment (PPE) is prescribed as a mandatory requirement in most sports where these impacts are likely to occur, though the methods of governance and evaluation criteria often do not accurately represent sports specific injury scenarios. One of the key shortcomings of such safety test standards is the human surrogate to which the PPE is affixed; this typically embodies unrepresentative geometries, masses, stiffness and levels of constraint when compared to humans. A key aspect of any human surrogate element is the simulant material used. Most previous sports specific surrogates tend to use off-the-shelf silicone blends to represent all the soft tissue structures within the human limb segment or organ; this approach potentially neglects important human response phenomena caused by the different tissue structures. This study presents an investigation into the use of bespoke additive cure Polydimethysiloxane (PDMS) silicone blends to match the reported mechanical properties of human relaxed and contracted skeletal muscle tissues. The silicone simulants have been tested in uniaxial compression through a range of strain rates and fit with a range of constitutive hyperelastic models (Mooney Rivlin, Ogden and Neo Hookean) and a viscoelastic Prony series. Graphical abstract: Highlights: Bespoke PDMS silicones formulated to better match relaxed and contracted muscle. PDMS simulants tested in uniaxial compression through a range of strain rates. Constitutive material models have been evaluated and fitted to experimental data.